Conceito constitucional da dignidade coletiva e efetivação dos direitos sociais - Souza, Michelle Amorim Sancho (2012)
This paper intends to demonstrate the constitutional concept of the dignity and collective relationship with the fulfillment of social rights. Thus, the definition of legal awareness and constitutional identity allows society to identify itself with the legal system. So that, this could be the overcoming of moral conscience and have universality as a fundamental characteristic, in the core society it captures the aspirations of certain primordial social body and reflects it, making it possible this recognition between society and especially the constitutional text. Therefore, the people, in its pluralistic greatness, is the holder of the construction/reconstruction of a given State's own constitutional discourse. In Brazil, the Brazilian ethnic generation was due to the junction of three people: Native American, African and European, who were responsible for bringing together in one legal system the ethnic, cultural and sociological pluralism, linked to the constant concern with intolerance to particular racial bias, realized from the preamble to the Constitution of 1988 (CF). From this perspective, through the processes of denial, metaphor and metonymy, the Brazilian constitutional identity is founded on the establishment of a democratic State of law and a building a society, free and fair (art. 1, caput c/c art. 3, I, CF). In addition, human dignity, one of the foundations of the Republic (art. 1, III, CF), is considered as the core value and most important source from which spring all the fundamental rights and duties. So in the constitutional context of Brazil, these three definitions form the theoretical framework for the construction of the constitutional concept of collective dignity, the need to face the gigantic duty of seeing the human being not as an individualized being, but as an ontologically in need of life in society. From this construction-dogmatic law, the fulfillment of social rights will go on by an analysis of unconstitutionality by omission, a defect that compromises the normative force of the Constitution. The recognition, of collective dignity therefore, will not allow this unconstitutionality to affect only the individual who is harmed by the lack of realization of social rights, but the whole social body.